Pengaruh Jenis Media Tanam dan Konsentrasi Air Kelapa Muda terhadap Pertumbuhan Setek Tanaman Tin (Ficus carica L.) - Suci Riska Nilam Sari; Rika Husna; Nurhayati Nurhayati (Jurnal Ilmiah Mahasiswa Pertanian, 2020)
Abstrak. Tujuan dari penelitian ini untuk mengetahui pengaruh jenis media tanam dan konsentrasi air kelapa muda, serta ada tidaknya interaksi keduanya terhadap pertumbuhan setek tanaman tin. Penelitian ini dilakukan dari bulan April hingga Juli 2019, di Rumah Kasa dan Laboratorium Fisiologi Tumbuhan Fakultas Pertanian. Rancangan penelitian yang digunakan ialah RAK pola faktorial 4 x 4 dengan 3 ulangan. Faktor yang diteliti ialah jenis media tanam terdiri 4 taraf (tanah + kompos, tanah + pupuk kandang, tanah + arang sekam, dan tanah + sekam padi) dan konsentrasi air kelapa muda terdiri 4 taraf (0%, 25%, 50% dan 75%). Hasil penelitian menunjukkan bahwa jenis media tanam berpengaruh terhadap panjang tunas, jumlah daun 30, 60 dan 90 HST, jumlah tunas 60 dan 90 HST, berat brangkasan kering, panjang akar, berat brangkasan basah, berat kering akar dan berat basah akar. Pertumbuhan setek tanaman tin terbaik dijumpai pada jenis media tanam tanah + kompos (1:1). Konsentrasi air kelapa muda berpengaruh terhadap jumlah daun, panjang tunas 30 HST, jumlah tunas 90 HST, berat brangkasan kering, panjang akar, berat brangkasan basah, berat kering akar dan berat basah akar. Pertumbuhan setek tanaman tin terbaik dijumpai pada konsentrasi air kelapa muda 75%. Terdapat interaksi antara jenis media tanam dan konsentrasi air kelapa muda terhadap jumlah tunas 60 dan 90 HST, panjang tunas 30, 60 dan 90 HST, jumlah daun 30 HST, berat brangkasan basah, berat brangkasan kering, panjang akar, berat basah akar dan berat kering akar. Pertumbuhan setek tanaman tin terbaik dijumpai pada kombinasi antara jenis media tanam tanah + kompos (1:1) dengan konsentrasi air kelapa muda 75%.The Effects of Types of Planting Media and Concentration of Green Coconut Water on the Growth of Cuttings of Fig Plants (Ficus carica L.)Abstract. The purpose of this study to determine the effects of the types of planting media and the concentration of green coconut water, as well as the interaction between the two on the growth of the cuttings of fig plants. This research was conducted at the Greenhouse and Plant Physiology Laboratory of the Faculty of Agriculture of Syiah Kuala University from April to July, 2019. The research design used was a randomized block design with the 4 x 4 factorial pattern and three replications. The factors studied were the planting media consisting of 4 different types, namely soil mixed with compost, soil mixed with manure, soil mixed with rice husk charcoal, and soil mixed with rice husk and the green coconut water concentration consisting of four levels, namely 0%, 25%, 50% and 75%. The results indicates that the treatment given to the planting media gave a significant effect on the length of the buds, the number of leaves in 30, 60 and 90 DAP, the number of buds in 60 and 90 DAP, the dry strover weight, the root length, the wet strover weight, the dry root weight and the wet root weight. Furthermore, it significantly affected the length of the buds in 30 DAP. The best growth of cuttings of fig plants is found in the type of soil mixed with compost (1: 1). The results also shows that the concentration of green coconut water also had a very significant effect on the number of leaves, length of the buds in 30 DAP, the number of buds in 90 DAP, the dry strover weight, the root length, the wet strover weight, the dry root weight, and the wet root weight. The best growth of cuttings of fig plants is found in concentration of green coconut water 75%. There was also an interaction found between the types of planting media and the concentration of green coconut water which had a very significant effect on the number of buds in 60 and 90 DAP, the length of the buds in 30, 60 and 90 DAP, the number of leaves in 30 DAP, the wet strover weight, the dry strover weight, the root length, the wet root weight and the dry root weight. The best growth of cuttings of fig plants is found in the combination of type of soil mixed with compost with concentration of green coconut water 75%.